Water Resources in the Canton of Latacunga Zona Urbana (Cotopaxi - Ecuador) (Ciencias de la Ingeniería y Aplicadas, 2023)
The objective of this research is to determine whether the Local Government of Latacunga Canton provides the necessary water resource to the five urban parishes of the Canton: Eloy Alfaro (San Felipe), Ignacio Flores (La Laguna), Juan Montalvo (San Sebastián), La Matriz (Centro), San Buenaventura (San Buenaventura) and in the same way if the population knows that the water it consumes is drinking water or only treated; in view of the fact that there are no drinking plants in the Canton; exploratory research carried out through the application of a survey carried out on the population of the urban parishes in question, the results show that the population does not know the quality of water it consumes and that there is an evident contamination of the Cutuchi River.
Keywords: Latacunga; Treated water; Urban areas; Water resource; Water; Cutuchi River